Modernised learning delivery strategies: The Canada School of Public Service technology integration project (Journal of Applied Learning and Teaching, 2018)
The Canada School of Public Service (CSPS) leadership expressed a desire to modernise online programme development and delivery in order to more effectively meet the School’s mandate. We conducted a review of modernised online programme development and delivery strategies, evaluated the School’s current progress against those strategies, and recommended an integrated set of proposed activities that would augment online presence for learners, identify and deliver key learning and performance support needs, increase the effectiveness of online CSPS programs and services, integrate online CSPS services with those from other departments, and implement continuous review and improvement for CSPS online services.